2024
DOI: 10.3390/foods13060963
|View full text |Cite
|
Sign up to set email alerts
|

Sea Cucumber Polysaccharide from Stichopus japonicu and Its Photocatalytic Degradation Product Alleviate Acute Alcoholic Liver Injury in Mice

Haoran Song,
Chen Song,
Chunhong Yan
et al.

Abstract: To prevent alcoholic liver disease, the addition of bioactive substances to the alcoholic drink Baijiu has been considered a feasible option. In the present study, the hepatoprotective effects of a sea cucumber sulfated polysaccharide (SCSP) isolated from Stichopus japonicu were investigated. Moreover, in order to enhance its solubility in an alcohol solution, it was depolymerized using a photocatalytic reaction, and the photocatalytic degradation products (dSCSPs) with an average molecular weight of less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In vivo experiments showed that the addition of either SCSP or dSCSP to Baijiu could alleviate alcoholic liver injury in mice, and dSCSP was more effective at reducing liver MDA levels. Therefore, the addition of sea cucumber polysaccharides or their low-molecular-weight derivatives to white wine helps to reduce alcoholic liver injury [45].…”
Section: Aldmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo experiments showed that the addition of either SCSP or dSCSP to Baijiu could alleviate alcoholic liver injury in mice, and dSCSP was more effective at reducing liver MDA levels. Therefore, the addition of sea cucumber polysaccharides or their low-molecular-weight derivatives to white wine helps to reduce alcoholic liver injury [45].…”
Section: Aldmentioning
confidence: 99%
“…Researchers identified a triphenyl derivative, CHNQD-00824 (44), from the marine fungus Aspergillus candidus, which was evaluated for cytotoxic activity against the HepG2 cell line and showed an IC50 value of 7.64 µM [114]. The marine-derived fungus Aspergillus candidus HM5-4, which was isolated from sponges in the South China Sea, was cultivated on solid rice medium, leading to the production of p-terphenyl derivatives-4″-deoxyterprenin (45). Notably, it exhibited cytotoxic effects against human liver cancer cells (BEL-7402), achieving an IC50 value of 6.69 µM, thereby demonstrating its potential as a promising anti-cancer agent [115].…”
Section: Hccmentioning
confidence: 99%